The clinical significance of PD-L1 in advanced gastric cancer is dependent on ARID1A mutations and ATM expression. (3rd August 2018) - Buglioni, Simonetta; Melucci, Elisa; Sperati, Francesca; Pallocca, Matteo; Terrenato, Irene; De Nicola, Francesca; Goeman, Frauke; Casini, Beatrice; Amoreo, Carla Azzurra; Gallo, Enzo; Diodoro, Maria Grazia; Pescarmona, Edoardo; et al.
ABSTRACT: Whether PD-L1 expression is associated with survival outcomes in gastric cancer (GC) is controversial. The inhibition of the PD-1/PD-L1 pathway is effective against genomically unstable tumors. Hypothesizing that also the clinical significance of PD-L1 might be dependent on the activation of molecular circuits ensuring genomic stability, we evaluated PD-L1 expression in tissue samples from 72 advanced GC patients treated with first-line chemotherapy. Samples were already characterized for DNA damage repair (DDR) component expression (pATM, pChk1, pWee1, γ-H2AX and pRPA2) along with mutations in DDR-linked genes ( TP53 and ARID1A ). Overall, PD-L1 expression was not associated with progression-free survival (PFS) and overall survival (OS), independently on whether we considered its expression in tumor cells (PD-L1-TCs) or in the immune infiltrate (PD-L1-TILs). In subgroup analysis, positive PD-L1-TC immunostaining was associated with better PFS in patients whose tumors did not carry DDR activation (multivariate Cox: HR 0.34, 95%CI: 0.15–0.76, p = 0.008). This subset (DDR off ) was characterized by negative pATM expression or the presence of ARID1A mutations. Conversely, the relationship between PD-L1-TC expression and PFS was lost in a molecular scenario denoting DDR activation (DDR on ), as defined by concomitant pATM expression and ARID1A wild-type form. Surprisingly, while PD-L1-TC expression was associated with better OS in the DDR off subset (multivariate Cox: HR 0.41, 95% CI: 0.17–0.96, p = 0.039), in the DDR on subgroup we observed an opposite impact on OS (multivariate Cox: HR 2.56, 95%CI: 1.06–6.16, p = 0.036). Thus, PD-L1-TC expression may impact survival outcomes in GC on the basis of the activation/inactivation of genome-safeguarding pathways.